Hope, Spirituality, Optimism, Pessimism, and Anxiety: A Kuwaiti-American Comparison - Abdel-Khalek, Ahmed (Research in the social scientific study of religion, 2010)
abdel-Khalek’s arabic Scale of optimism and pessimism and Kuwait university anxiety Scale were translated into english. Scioli’s (2007) multidimensional trait hope scale was translated into arabic. results obtained from 211 american and Kuwaiti young adults confirmed the applicability of the Scioli Hope scale in an arabic sample while re-confirming the value of the abdel-Khalek scales for english samples. Greater optimism and overall hope was reported by Kuwaitis as compared to americans. while Kuwaitis reported greater spiritualized hope, american reported greater non-spiritualized hope. For Kuwaitis, but not americans, greater spiritualized hope was associated with less pessimism and anxiety. For Kuwaitis and americans, hope derived from spiritual integrity was the strongest correlate of greater optimism as well as lower pessimism and anxiety.